(untitled) (Journal of Economic Research & Business Administration, 2016)
The modern banking practice includes different types of payment transactions. The current national payment system in Kazakhstan which is operated by the Republican state enterprise “Kazakhstan center of inter-bank settlements of National Bank of Kazakhstan” is an Interbank system of money transfer and Interbank clearing system. They are characterized by the presence of a significant and complete legal framework, a high degree of safety and reliability of the information solutions employed. The article contains the analysis, which helps to determine the most convenient forms of service for different categories of clients of commercial banks, as well as to determine the role of each payment system in the overall clearing system in Kazakhstan.